Problematika dan Tantangan Pendidikan Islam di Era Globalisasi - Keisya Angie Nurul Fatihah; Noviani Hidayah; Muhammad Afdhal Ridho; Ajahari Ajahari (YASIN, 2026)
Although various studies have discussed the impact of globalization on Islamic education, integrative studies that comprehensively map the problems and challenges of Islamic education remain limited. This study aims to identify and classify the main problems of Islamic education in the era of globalization, analyze the challenges faced from a multidisciplinary perspective, and formulate strategic recommendations to strengthen the relevance and sustainability of Islamic education. This study used a qualitative approach with a systematic literature review design. Data were collected through systematic searching, screening, eligibility assessment, and critical review of relevant books and scholarly articles. Data were analyzed using content analysis techniques combined with critical comparison to identify the main themes and explain the interrelationships among findings systemically. The results show five interrelated main problems, namely the dichotomy between religious and general sciences, students’ identity crisis, low educator competence, digital infrastructure gaps, and a curriculum that is not yet adaptive to changing times. These five issues form a complex system and weaken the ability of Islamic educational institutions to respond effectively to global dynamics. The recommended strategies include the integration of knowledge based on Islamic epistemology, the strengthening of contextual character education, the improvement of educators’ digital competence, equitable access to technology, and curriculum redesign based on learning outcomes and future competencies. This study contributes theoretically through the development of a comprehensive conceptual framework on the challenges of Islamic education and has practical implications for policymakers, educational institutions, and educators in developing an Islamic education system that is adaptive, grounded in Islamic values, and sustainable.